2019
DOI: 10.3390/en12142779
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement Effect of Bimetallic Amide K2Mn(NH2)4 and In-Situ Formed KH and Mn4N on the Dehydrogenation/Hydrogenation Properties of Li–Mg–N–H System

Abstract: In this work, we investigated the influence of the K2Mn(NH2)4 additive on the hydrogen sorption properties of the Mg(NH2)2 + 2LiH (Li–Mg–N–H) system. The addition of 5 mol% of K2Mn(NH2)4 to the Li–Mg–N–H system leads to a decrease of the dehydrogenation peak temperature from 200 °C to 172 °C compared to the pristine sample. This sample exhibits a constant hydrogen storage capacity of 4.2 wt.% over 25 dehydrogenation/rehydrogenation cycles. Besides that, the in-situ synchrotron powder X-ray diffraction analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…This interaction is slightly improved with increased KH amount, since the rate constant values are rising gradually. These outcomes agree with the results from our previous work, where another potassium compound is used as an additive: K 2 Mn(NH 2 ) 4 [11].…”
Section: Thermal Behaviour and Reaction Kineticssupporting
confidence: 92%
See 1 more Smart Citation
“…This interaction is slightly improved with increased KH amount, since the rate constant values are rising gradually. These outcomes agree with the results from our previous work, where another potassium compound is used as an additive: K 2 Mn(NH 2 ) 4 [11].…”
Section: Thermal Behaviour and Reaction Kineticssupporting
confidence: 92%
“…The poor reaction kinetics are caused by species diffusion at the amide-hydride contacts, as well as nucleation and development of imide phases [7]. In order to accelerate the reaction kinetics, several additives have been investigated so far [8][9][10][11][12][13][14][15]. K-based compounds have consistently been one of the most effective additives [16].…”
Section: Introductionmentioning
confidence: 99%
“…30 Gizer then used a type of bimetallic amide for the enhancement of dehydrogenation kinetics. 31 Shukla obtained excellent hydrogen sorption with the Li−Mg−N−H system using Li 4 BH 4 (NH 2 ) 3 and carbon nanostructures. 32 Yang et al proposed a ternary mixture system comprising an amide (LiNH 2 ), a borohydride (LiBH 4 ), and a metal hydride (MgH 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the doped LiBH 4 formed Li 4 BH 4 (NH 2 ) 3 with the desorption intermediate LiNH 2 from the starting amide and hydride. , Later, other metal borohydrides were tested individually or as a component, as well as a dopant in the hydrogen-storage systems. , Wang doped potassium hydride to the system and remarkably reduced the temperature for dehydrogenation . Gizer then used a type of bimetallic amide for the enhancement of dehydrogenation kinetics . Shukla obtained excellent hydrogen sorption with the Li–Mg–N–H system using Li 4 BH 4 (NH 2 ) 3 and carbon nanostructures .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of selected additives/catalysts has been proven to be a successful strategy to improve the hydrogen storage performance of amide-hydride systems [29][30][31][32][33][34][35][36][37][38][39][40]. Transition metals such as Sc, Ti, V, Ta, Ni, and their compounds are known to be effective additives for improving the properties of amide-hydride systems [26,[41][42][43][44][45][46]. Ichikawa et al [42,43] first reported on the beneficial effect that the addition of nano-sized Ti additives entails on the LiNH 2 -LiH system.…”
Section: Introductionmentioning
confidence: 99%